Comparison of SARS-CoV2 IgG Antibody Levels in Health Workers with and without a History of COVID-19 Infection after Heterologous Vaccination at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia - Ferda Puspalina; Nova Kurniati; Eddy Mart Salim; Yuniza; Zen Ahmad (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: The COVID-19 pandemic, which has spread very quickly, has created crises in all aspects of life around the world. The administration of the COVID-19 heterologous vaccine in Indonesia is prioritized for high-risk groups, one of which is health workers. This study aimed to determine the comparison of quantitative IgG antibody levels for SARS CoV2 between health workers with and without a history of being infected with COVID-19 after heterology vaccination at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia. Methods: This study was a cross-sectional analytic observational study. A total of 64 subjects participated in this study. Data analysis was carried out with the help of SPSS software in univariate and bivariate. Results: SARS-CoV2 IgG antibody levels with and without a history of being infected with COVID-19 after heterologous vaccination did not find a significant difference in IgG levels between the two groups. However, the quantitative IgG levels of SARS-CoV2 in the infected history group were greater, namely 4834.25 AU/mL, compared to no history of COVID-19 infection of 3833.35 AU/mL Conclusion: There is a difference in the average SARS-CoV 2 IgG between subjects with a history of being infected with COVID-19 and without a history of COVID-19 at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia, although statistically, it is not significantly different.